Characterisation of trials where marketing purposes have been influential in study design: a descriptive study. Issue 1 (December 2016) - Barbour, Virginia; Burch, Druin; Godlee, Fiona; Heneghan, Carl; Lehman, Richard; Perera, Rafael; Ross, Joseph; Schroter, Sara
Abstract Background Analysis of trial documentation has revealed that some industry-funded trials may be done more for marketing purposes than scientific endeavour. We aimed to define characteristics of drug trials that appear to be influenced by marketing considerations and estimate their prevalence. Methods We examined reports of randomised controlled trials of drugs published in six general medical journals in 2011. Six investigators independently reviewed all publications, characterising them as YES/MAYBE/NO suspected marketing trials, and then met to reach consensus. Blinded researchers then extracted key trial characteristics. We used blinded cluster analysis to determine if key variables could characterise the categories of trials (YES/MAYBE/NO). Results 41/194 (21 %) trials were categorised as YES, 14 (7 %) as MAYBE, 139 (72 %) as NO. All YES and MAYBE trials were funded by the manufacturer, compared with 37 % of NO trials (p  < 0.001). A higher proportion of YES trials had authors or contributors from the manufacturer involved in study design (83 % vs. 19 %), data analysis (85 % vs.15 %) and reporting (81 % vs. 15 %) than NO trials (p  < 0.001). There was no significant difference between groups in the median number of participants screened (p  = 0.49), but the median number of centres recruiting participants was higher for YES compared with NO trials (171 vs. 13, p  < 0.001). YES trials were not more likely to use a surrogate (42 % vs. 30 %;p  = 0.38) or composite primary outcome measure (34 % vs. 19 %;p  = 0.14) than NO trials. YES trials were often better reported in terms of blinding, safety outcomes and adverse events than NO trials. YES trials more frequently included speculation that might encourage clinicians to use the intervention outside of the study population compared to NO trials (59 % vs.37 %, p  = 0.03). Cluster analysis based on study characteristics did not identify a clear variable structure that accurately characterised YES/MAYBE/NO trials. Conclusions We reached consensus that a fifth of drug trials published in the highest impact general medical journals in 2011 had features that were suggestive of being designed for marketing purposes. Each of the marketing trials appeared to have a unique combination of features reported in the journal publications.